A STUDY TO ASSESS THE KNOWLEDGE AND ATTITUDE REGARDING MENOPAUSE AMONG PERI-MENOPAUSAL WOMEN AT BANAR AND BHADVASIYA COMMUNITY HEALTH CENTERS, JODHPUR - Pooja Choudhary,; Annamma Sumon, (EPRA International Journal of Research and Development (IJRD), 2022)
INTRODUCTION: Menopause, also known as the climacteric, is the time in most women's lives when menstrual periods stop permanently, and they are no longer able to bear children. Menopause typically occurs between 49 and 52 years of age. Medical professionals often define menopause as having occurred when a woman has not had any menstrual bleeding for a year. It may also be defined by a decrease in hormone production by the ovaries. In those who have had surgery to remove their uterus but still have ovaries, menopause may be considered to have occurred at the time of the surgery or when their hormone levels fell. Following the removal of the uterus, symptoms typically occur earlier, at an average of 45 years of age. AIM OF THE STUDY: Assess knowledge and attitude regarding menopause among peri menopausal women. MATERIAL AND METHOD: non experimental - descriptive research design study was used in order to evaluate knowledge and attitude regarding menopause among peri menopausal women of selected by non-probability purposive sampling technique in community centers Jodhpur. Each participant was informed about the study and that they could withdraw at any time and a written consent was also obtained. RESULT: The findings showed majority of women had inadequate knowledge regarding menopause The knowledge scores of peri-menopausal women on menopause among total numbers of sample (100), 59 (59%) sample had inadequate knowledge, 23 (23%) of sample had moderately adequate knowledge and 18 (18%) of sample had adequate knowledge regarding menopause among peri-menopausal women. However, no significant association exist between knowledge level and attitude level regarding menopause with their selected demographic variables such as Age, Marital status, Number of children, Type of family, Occupation, Age of menarche, Family history of menopausal problems. CONCLUSION: It can be concluded that peri menopausal had inadequate knowledge as per current research recommendations. Therefore, on understanding of menopause and how it causes changes in the women’s body is not only relevant to the women but also who provides health services. Menopausal health has been one of the neglected areas in our country and needs timely vital attention. The need of the hour is to conduct awareness campaigns to inform general public about menopause. The present study was undertaken to assess the knowledge and attitude regarding menopause among peri-menopausal women at Banar and Bhadvasiya Community health centers, Jodhpur.